Política pesqueira e os territórios dos pescadores artesanais de Bitupitá, Barroquinha, Ceará - Arruda, Emerson Alves (2020)
On Bitupitá beach, the fishing weirs have been present since 1869 and are basic pieces of the community's territoriality. A rich set of traditional knowledge and techniques, in addition to their governance mechanisms, characterize the fishing in the community, which already had 123 of these traps registered in the 1990s. In 2019, 42 fishing weirs were mapped in the Bitupitá Sea, on which more than 1/3 of the district's population depends. The prohibition of these traps puts in check the principles of environmental justice, leading to an unprecedented situation of conflict between the community and the state. The main goal of this study is to analyze the role of corral fishing for the community of Bitupitá beach in the face of the conflict between the legal system and the reproduction of the community's way of life. To this end, interviews were conducted with fishermen, corral owners, and traversers to build a socio-economic panorama of those directly involved with fishing, in addition to demonstrating the commercialization network and production chain coming from the fishing corrals. The analysis of the interviews allowed us to see how the corral fishery influences the community territory, besides, to glimpse the degree of dependence of the community on the corral fishery. The information from this research aims to serve as a subsidy for the formulation of a proposal for sustainable management of the fishery, which allows for self-monitoring and participatory management of the corral fisheries in the state of Ceará.